P18 Pemigatinib for previously treated locally advanced or metastatic cholangiocarcinoma: final results from FIGHT-202. (20th September 2022) - Vogel, Arndt; Sahai, Vaibhav; Hollebecque, Antoine; Vaccaro, Gina M; Melisi, Davide; Rajabi, Raed MAl; Paulson, Andrew S; Borad, Mitesh J; Gallinson, David; Murphy, Adrian G; Oh, Do-Youn; Dotan, Efrat; et al.
Abstract : Cholangiocarcinoma (CCA) tumors have high genomic heterogeneity, with 40%–50% of patients with CCA harboring ≥1 clinically-actionable genetic alteration, including fibroblast growth factor receptor (FGFR)1–3 alterations. Pemigatinib is an oral, potent, selective FGFR1–3 inhibitor for the treatment of adults with previously treated, unresectable, locally advanced/metastatic CCA with an FGFR2 fusion or other rearrangement. Here we report the final results from an open-label, single-arm, multicenter phase 2 study evaluating the safety and efficacy of pemigatinib in patients with previously treated locally advanced or metastatic CCA (FIGHT-202; NCT02924376 ; EudraCT Number: 2016–002422-36). Eligible patients were ≥18 years old, with locally advanced/metastatic or surgically unresectable CCA that progressed after ≥1 prior therapy, documented FGF/FGFR status, Eastern Cooperative Oncology Group performance status ≤2, and adequate hepatic/renal function. Patients were separated into 3 cohorts based on confirmed FGF/FGFR status (cohort A, FGFR2 fusions or rearrangements; cohort B, other FGF/FGFR genetic alterations; cohort C, no FGF/FGFR genetic alterations). All patients received 13.5 mg pemigatinib once daily (2 weeks on/1 week off) until disease progression or unacceptable toxicity. The primary endpoint was overall response rate (ORR) in cohort A, as confirmed by independent central review. Secondary endpoints included ORR in cohorts B and C, duration of response, disease control rate, progression-free survival, overall survival, and safety across all cohorts. Overall, 147 patients were enrolled (cohort A, n=108; cohort B, n=20; cohort C, n=17; undetermined FGF/FGFR status, n=2). Median (range) age was 59.0 (26–78) years, 57.8% of patients were women, 70.7% were White, and 89.8% had intrahepatic CCA, including 99.1% in cohort A. Median (range) duration of follow-up was 45.4 (19.9–53.7) months. In total, 98.6% of patients discontinued treatment, most commonly for disease progression (n=105/147; 71.4%). In cohort A, ORR (95% CI) was 37.0% (27.9%–46.9%). Efficacy results are provided in the table 1 . All patients reported treatment-emergent adverse events (TEAEs); the most common were hyperphosphataemia (58.5%), alopecia (49.7%), and diarrhoea (47.6%). Most TEAEs were grade 1/2 in severity; the most common grade ≥3 TEAE was hypophosphataemia (14.3%). Additionally, 91.8% of patients had a treatment-related AE, 4.1% had a fatal TEAE (all considered unrelated to pemigatinib treatment), and 10.2% discontinued pemigatinib due to a TEAE. In this analysis, pemigatinib continued to demonstrate durable response, prolonged survival, and a manageable safety profile in patients with advanced/metastatic CCA with FGFR2 fusions or rearrangements. These results further highlight the need for molecular testing in patients with CCA.